Factors that trigger the structuring process of Management Control in SMEs : An analysis based on the theory of growth thresholds - (:unkn) unknown (My University, 2021)
The question of when to introduce management control (MC or CDG in french) as a management tool has arisen in recent years in SMEs in sub-Saharan Africa in view of the difficulties they face during the launch phase and to initiate growth. Thorough studies of 8 Cameroonian SMEs tend to show that, contrary to what the growth threshold theory suggests, the factors that favour the structuring of CDG in SMEs are not only linked to the increase insize, the age of the company or the number of entity or agency. This article shows that the need for the structuring of the CDG in the Cameroonian SME arises when it faces irrational staff behaviour, during the deployment of the strategy and the implementation of innovations.
Keywords: African Research